Un an de lectură și cultură în bibliotecile din raionul Hîncești: retrospectiva ediției a VIII-a a Programului național „LecturaCentral” - DARII, Tatiana (BIBLIOPOLIS, 2026)
The article reflects the essential moments of the 8th edition (2025) of the National Program LecturaCentral within the activities organized and carried out in the public libraries of the Hîncești district, which aimed to promote books and reading among the communities they serve. This Program demonstrated, once again, the importance of collaboration between libraries, writers and other partners in the reading segment as a means of promoting education, personal and cultural development. The need for investments in book purchases, modern technologies and human resources was also reiterated.